Investigation of potential groundwater sources using electrical resistivity imaging for industrial facilities in Gebeng, Kuantan, Malaysia: A case study - Sarbani, Daud; Mohd Fakhrurrazi, Ishak; Puteri Izrina, Ismi; Muhammad Farhan, Zolkepli (Geological Society of Malaysia, 2025)
In dry regions with limited access to surface water, groundwater is an essential source of freshwater supplies. This is especially true in areas where there is limited availability of surface water. Industries such as manufacturing make extensive use of water for various purposes, including cleaning, heating, and cooling, the production of steam, use as a solvent, transportation of substances that have been dispersed into it, and as a component of the manufactured product itself. Because of its large size, the groundwater reserve has the potential to become an additional source of water supply for the country, particularly in industrialized regions. The geophysical approach, which geophysicists dominate, has become one of the most prominent methods researchers use to offer the best technique in mineral or resources exploration. Electrical Resistivity Imaging, more commonly referred as ERI, is one of the geophysical techniques that offers a very intriguing method for determining subsurface profiles across a wider region. The primary purpose of this assessment is to assess a potential groundwater aquifer and determine whether it might be economically viable in industrial development facilities. The method described above is suitable for investigating various subsurface conditions. ERI’s groundwater investigation using alternative methods, which enhance standard methods, could provide complete and convincing findings, increase efficiency in costing and timing. The ERI survey was carried out with the assistance of an ABEM LS2 Terrameter, which featured 61 electrodes that were planted along a line 400 meters long Line 1, with an electrode spacing of 5 meters (inner) and 10 meters (outer). When the survey was done on Line 2, the electrode spacing was set at 2.5 meters (inner) and 5 meters (outer). The results of the ERI tests indicate that Lines 1 and 2 are good indicators of groundwater presence. Line 2 was undertaken with a length of 200 meter rather than 400 meters, resulting in less data (shallow depth) being obtained. Furthermore, groundwater would have low resistivity (20 to 200 Ωm). An ERI provided a very significantly by enhances groundwater investigations by providing detailed subsurface information that aids in locating and managing water resources effectively. Its ability to integrate with other data sources, coupled with its cost-effectiveness and efficiency that make it an invaluable tool in hydrogeology and environmental management.